Evaluation of lactation models in pasture-based dairy ewes in Bosnia and Herzegovina - Šalamon, Dragica; Batinić, Vinko; Ivanković, Stanko, agronom; Antunac, Neven; Džidić, Alen (2020)
Milk of Kupres, Privor and Stolac dairy ewe breeds is used for the production of the fine cheese varieties. To the best of our knowledge there are no information about milk production and milk composition of these pasture-based dairy ewes. The aim was to determine the best lactation curve model in autochthonous pasture-based dairy ewes in Bosnia and Herzegovina. Milk production was recorded and milk composition sampled (milk fat and protein) during early, mid and late lactation in 129 Kupres, 141 Privor and 129 Stolac pramenka ewes. Four lactation models (Wilmink, Cubic, Ali-Shaeffer and Guo-Swalve) were compared and selected based on the lowest coefficient of determination and root mean square error. The Guo-Swalve model described all of the measured variables most successfully. Kupres pramenka dairy ewe was the highest producing breed with 139 kg of milk during 175 days of lactation (0.79 kg/d; between lactation day 50 to 225) and showed the standard lactation curve. Privor pramenka produced 118 kg of milk during 175 days of lactation (0.67 kg/d) and Stolac pramenka 101 kg of milk during 175 days of lactation (0.58 kg/d). Both showed atypical constantly decreasing shape of the lactation curve common in low producing dairy ewes. The prediction of milk yield and milk composition from the Guo-Swalve model could be used by the national breeding program for the Kupres, Privor and Stolac pramenka sheep breeds. Additional research during a more stable management conditions is recommended for Privor and Stolac pramenka.
Mlijeko kupreške, privorske i stolačke pramenke koristi se za proizvodnju kvalitetnih sireva. Zbog nedostatka znanja o količini i sastavu mlijeka ovih autohtonih bosanskohercegovačkih pasmina ovaca cilj je bio odrediti najbolji model koji opisuje njihove laktacije. Uzorci za količinu i sastav mlijeka (mliječna mast i protein) prikupljeni su u ranoj, srednjoj i kasnoj laktaciji te je bilježena količina mlijeka za 129 kupreških, 141 privorskih i 129 stolačkih pramenki. Uspoređena su četiri modela laktacijskih krivulja (Wilmink, kubni, Ali-Shaeffer i Guo-Swalve) i najprimjenjiviji model je biran temeljem najvećeg koeficijenta determinacije i najmanjeg korijena srednje kvadratne pogreške. Guo-Swalve model je najuspješnije opisao sve varijable. Kupreška pramenka pokazala se kao pasmina s najvećom proizvodnjom od 139 kg mlijeka u 175 dana laktacije (0,79 kg/d; između 50-og i 225-og dana laktacije) i standardnom laktacijskom krivuljom. Privorska pramenka je proizvela 118 kg mlijeka u 175 dana laktacije (0,67 kg/d), a Stolačka pramenka 101 kg mlijeka u 175 dana laktacije (0,58 kg/d). Laktaciju stolačke i privorske pasmine karakterizira atipična laktacijska krivulja koja je u stalnom padu i karakteristična je za ovce koje nisu selekcionirane za proizvodnju mlijeka. Predviđanje količine i sastava mlijeka Guo-Swalve modelom moglo bi se koristiti u uzgojnom programu za kuprešku, privorsku i stolačku pramenku. Navedeni modeli se trebaju koristiti za privorsku i stolačku pramenku s oprezom jer njihova proizvodnja mlijeka tijekom laktacije je vrlo varijabilna.
Bibliografija: 34 jed.
Summary ; Sažetak.
Keywords: Mlijeko -- Ovčje mlijeko -- Sastav mlijeka -- Laktacija -- Autohtone pasmine ovaca